Partial Fractions and Integration

Verified

Added on  2022/11/27

|22
|4730
|305
AI Summary
This document explains the concept of partial fractions and integration. It provides step-by-step solutions for finding the partial fractions and evaluating the integral of a rational function. The domain and intercepts of the given function are also determined.
tabler-icon-diamond-filled.svg

Contribute Materials

Your contribution can guide someone’s learning journey. Share your documents today.
Document Page
Q 1.
Answer
a)
i)
g(x, y) = D[x, y]0 = (2x, 7y)
By simple inspection, the transformation matrix A is found as
D = 2 0
0 7
This is verified as
g(x, y) = 2 0
0 7 · x
y = 2x
7y
D is a scaling matrix.
ii)
h(x, y) = B · [x, y]0 = (x, 3x + y)
By simple inspection, the transformation matrix B is found as
B = 1 0
3 1
This is verified as
h(x, y) = 1 0
3 1 · x
y = x
3x + y
B is a shearing matrix with y shearing factor of 3.
iii)
k(x, y) = C · [x, y]0 = (y, x)
By simple inspection, the transformation matrix C is found as
C = 0 1
1 0
1
tabler-icon-diamond-filled.svg

Secure Best Marks with AI Grader

Need help grading? Try our AI Grader for instant feedback on your assignments.
Document Page
This is verified as
k(x, y) = 0 1
1 0 · x
y = y
x
C is a reflection matrix through line y = x.
b)
The composition transformation required is
f = k ◦ h ◦ g
Applying the transformation to a vector x in R2. Therefore,
f (x) = (k ◦ h ◦ g)(x) = k(h(g(x)) = C(B(D · x))) = CBD(x)
Since, f (x) = A · x, we have
A = CBD
Matrix A is evaluated by matrix multiplication in the following way
A = CBD
= 0 1
1 0 × 1 0
3 1 × 2 0
0 7
= 0 1
1 0 × 2 0
6 7
= 6 7
2 0
c)
A transformation is invertible ifthe matrix oftransformation is invertible,
that is the matrix has a non zero determinant (Clark and Mccune, 2013).
A is the matrix of transformation f .It’s determinant is
det(A) = 6 7
2 0 = (6 × 0) (2 × 14) = 14
2
Document Page
Therefore, A is invertible.
Inverse of a 2d invertible matrix
M = a b
c d
is given by
M 1 = 1
det(M )
d b
c a
Therefore, inverse of A, which represents the transformation f1 is
A1 = 1
14
0 7
2 6
d)
Let C0be a image in R2 to which the transformation f maps the unit circle C.
C0 = f(C)
Taking inverse on both sides
f 1(C0
) = C
Thus the inverse transformation maps the points on C0 back to the unit circle
C: x2 + y2 = 1.
Now, for a vector x in R2
f 1(x) = A1 · x = 1
14
0 7
2 6 · x
y = 1
14
7y
2x + 6y
This transformation maps back to the unit circle, therefore
1
14
(7y)
2
+ 1
14
(2x + 6y)
2
= 1
Simplifying
49y2 + 36y2 24xy + 4x2 = 142
or
4x2 24xy + 85y2 = 142
3
Document Page
is the required equation of the image f (C).
e)
Area of the image f (C) is obtained using a simple property of transformation
Area of f (C) = ||det(A)|| × Area of C
where, A is the matrix of transformation of f .
For the given transformation f ,determinant oftransformation matrix was
calculated (refer c) as:det(A) = 14,which implies ||det(A)|| = 14.Since
the area of unit circle C is π, therefore
Area of f(C) = 14 × π = 14π
Q 2.
Answer
a)
i)
f maps points (0,0), (1,0) and (0,1) into points (3,3), (3,4) and (4,3).
Let, x’ represent the transformed coordinates of point x.Therefore,
x’ = f(x) = A · x + a
Let A be any arbitrary matrix
A = a1 a2
b1 b2
and a be a vector [c1, c2]T .
For the transformation (0, 0) (3, 3), we get
(3, 3)T = A · (0, 0)T + (c1, c2)T
Implies, (c1, c2)T = (3, 3)T .
For the transformation (1, 0) (3, 4), we get
(3, 4)T = a1 a2
b1 b2
· (1, 0)T + (3, 3)T
4
tabler-icon-diamond-filled.svg

Secure Best Marks with AI Grader

Need help grading? Try our AI Grader for instant feedback on your assignments.
Document Page
Implies, a1 + 3 = 3 =⇒ a1 = 0 and b1 + 3 = 4 =⇒ b1 = 1.
For the transformation (0, 1) (4, 3), we get
(4, 3)T = 0 a2
1 b2
· (0, 1)T + (3, 3)T
Implies, a2 + 3 = 4 =⇒ a2 = 1 and b2 + 3 = 3 =⇒ b2 = 0.
Therefore, the transformation f is completely determined as
f = 0 1
1 0 · (x, y)T + (3, 3)T
ii)
The are no fixed points visible in the transformation f .The transformation
is combination of translation,which happens 3 units along the line y = x,
as given by a and then reflection in the line y = x,as given by matrix A,
therefore, it is a case of glide-reflection.
b)
Reflection in the line y = −x + 5.
To achieve this transformation, the idea is to translate everything to the ori-
gin, reflect about the line y = −x and then move everything back.
Let us translate everything to origin using the transformation
x’ = x + h
where, h = (0, −5)T , is the translation vector.
Since we are at the origin, reflect in the line y = −x.This is achieved using
transformation matrix
A = 0 1
1 0
Therefore, the resulting transformation is
A(x + h) = 0 1
1 0 x + 0
5 = 0 1
1 0 · x + 5
0
The final step is to move everything back to the originallocation which
is achieved by translating x by 5.This is achieved by the inverse vector
5
Document Page
h1 = (0, 5)T . Therefore, the final transformation k, is
k = A(x + h) + h1 = 0 1
1 0 · x + 5
0 + 0
5 = 0 1
1 0 · x + 5
5
| {z }
Ax+b
which is the required form of the transformation k.
Q 3.
2x3 3x2 18x + 17
x2 3x − 4
Answer
a) Partial fractions
Since, for the given rational function, the degree of numerator is greater than
the degree of denominator, the function is first simplified by polynomial di-
vision in the following way
2x + 3
x2 3x − 4 2x3 3x2 18x + 17
2x3 6x2 8x
3x2 10x + 17
3x2 9x − 12
x + 29
Therefore, the rational function is simplified as
2x3 3x2 18x + 17
x2 3x − 4 = 2x + 3 + 29 − x
x2 3x − 4
In this simplified, partial fractions of only the last term (rational) has to be
determined.
6
Document Page
Factorize x2 3x − 4 as (x − 4)(x + 1).
29 − x
x2 3x − 4
= 29 − x
(x − 4)(x + 1)
29 − x
(x − 4)(x + 1)
= A
x − 4+ B
x + 1
= A(x + 1) + B(x − 4)
(x − 4)(x + 1)
[Equating numerators]
29 − x = (A + B)x + (A − 4B)
[Equating coefficients of like terms on both sides]
29 = A − 4B (1)
1 = A + B (2)
[(1) and (2) are solved simultaneously]
A = 5 & B = 6
2x3 3x2 18x + 17
x2 3x − 4 = 2x + 3 + 5
x − 4 6
x + 1
b)
c)
Integral to be evaluated is
Z 2x3 3x2 18x + 17
x2 3x − 4 dx
7
tabler-icon-diamond-filled.svg

Paraphrase This Document

Need a fresh take? Get an instant paraphrase of this document with our AI Paraphraser
Document Page
In order to evaluate the integral, the rational fraction is first expressed in the
partial fraction as obtained in part a).Therefore,
Z 2x3 3x2 18x + 17
x2 3x − 4 dx =
Z
2x + 3 + 5
x − 4 6
x + 1dx
[Taking integration to individual terms]
=
Z
2x dx +
Z
3 dx +
Z 5
x − 4dx −
Z 6
x + 1dx
[
Z
xn = xn+1
n + 1 =
Z
2x = x2]
[
Z
k = kc =
Z
3 = 3x]
= x2 + 3x +
Z 5
x − 4dx −
Z 6
x + 1dx
[Substitute: x − 4 = u & x + 1 = v]
= x2 + 3x + 5
Z 1
u du − 6
Z 1
v dv
[Standard Int.:
Z 1
x = ln x]
= x2 + 3x + 5 ln u − 6 ln v + C
[Back substitute: u = x − 4 & v = x + 1]

Z 2x3 3x2 18x + 17
x2 3x − 4 dx = x2 + 3x + 5 ln (x − 4) 6 ln (x + 1) + C
Q 4.
f (x) = x + 1
x2 + 8
Answer
a) Domain and intercept
8
Document Page
Domain :For a function of single variable x, domain is the set of all inputs
for which the function f (x) is well defined.
Since for the given f (x),the denominator is always positive and never be-
comes 0, the function is set of all real numbers R.
Domain of f (x):(−∞, ∞)
Intercepts:The x- intercept(s) of f (x) is obtained by setting f (x) = 0 and
the y- intercept of f (x) is obtained by setting x = 0 in f (x).
x- intercept:
f (x) = 0
= x + 1
x2 + 8= 0
[x2 + 8 6= 0]
x + 1 = 0 =⇒ x = 1
Therefore, x = 1 or (1, 0) is the x- intercept.
y- intercept:
f (x) = 0 + 1
0 + 8= 1
8
Therefore, y =1
8 or 0,1
8 is the y- intercept.
b) Find f0
(x)
f (x) = x + 1
x2 + 8
Since f (x) is rational function, use Product Rule to find the derivative:
Product Rule :d
dx
u
v = vu0 uv0
v2
9
Document Page
For the given f (x), u = x + 1 and v = x2 + 8.Therefore
f 0
(x) = (x2 + 8)(x + 1)0 (x + 1)(x2 + 8)0
(x2 + 8)2
[Derivatives : (x + 1)0 = 1 & (x 2 + 8)0 = 2x]
= (x2 + 8) (x + 1)(2x)
(x2 + 8)2
= x2 + 8 2x2 2x
(x2 + 8)2
f 0
(x) = 8 − x2 2x
(x2 + 8)2
c) Stationary points
Stationary point(s) of a function f (x) is determined by setting f0
(x) = 0.
For the given f (x), we have
f 0
(x) = 8 − x2 2x
(x2 + 8)2
For the stationary points therefore
f 0
(x) = 0
= 8 − x2 2x
(x2 + 8)2 = 0
[The denominator: (x2 + 8)2 > 0]
= 8 − x2 2x = 0
(x + 4)(x − 2) = 0
x = 4 or x = 2
For x = 4,
f (x) = 4 + 1
16 + 8
= 0.125
For x = 2,
f (x) = 2 + 1
4 + 8
= 0.25
10
tabler-icon-diamond-filled.svg

Secure Best Marks with AI Grader

Need help grading? Try our AI Grader for instant feedback on your assignments.
Document Page
The stationary points of f (x) therefore are:(4, −0.125) and (2, 0.25).
x x < −4 : x = 54 < x < 2 : x = 0x > 2 : x = 3
f 0
(x) 6.43 × 103 0.125 0.024
From the sign of f0
(x) it is clear that f (x) is decreasing in the interval x < −4,
then increasing in the interval 4 < x < 2 and then decreasing for x > 2.
This suggests that x = 4 or the point (4, −0.125) is absolute minimum of
f (x) and x = 2 or the point (2, 0.25) is absolute maximum (Stewart, Redlin,
Watson and Panman, 2017).
d) Equation of asymptotes
Vertical asymptote:Equation of vertical asymptote of a rational function
is obtained by setting the denominator equal to 0.
For the given f (x), the denominator x2 + 8 has no real roots, therefore, f (x)
has no vertical asymptotes.
Horizontalasymptote:Equation of horizontalasymptote is obtained by
solving the limit
lim
x→∞ f (x)
For the given f (x)
lim
x→∞ f (x) = lim
x→∞
x + 1
x2 + 8= lim
x→∞
1
x + 1
x2
1 + 8
x2
= 0
The horizontal asymptote of f (x) therefore is y = 0, or the x- axis.
e) Odd, even or neither
A function g(x) is odd if g(−x) = −g(x), or even if g(−x) = g(x), or neither
if both conditions are false.For the given function f (x)
f(−x) = (−x) + 1
(−x)2 + 8= x + 1
x2 + 8
f (−x) 6= −f (x), also f (−x) 6= f (x).Therefore, f (x) is neither odd nor even.
f ) Sketch of f (x)
11
Document Page
In order to plot the function, we prepare a table of (x, f (x)), for few impor-
tant points and then plot them on a graph.
x f (x)
5 0.12
4 0.125
1 0
0 0.125
2 0.25
4 0.21
Figure 1:Sketch of f(x)
Q 5.
Answer
a)
Evaluate the integral Z
cosh5 x dx
Trig. Identity
cosh2 x = 1 + sinh2 x
12
Document Page
Therefore,
Z
cosh5 x dx =
Z
cosh x(cosh2 x)2 dx
=
Z
cosh x(1 + sinh2 x)2 dx
[Substitute:sinh x = u = cosh x dx = du]
=
Z
(1 + u2)2 du
=
Z
1 + 2u2 + u4 du
[Standard Int. :
Z
un = un+1
n + 1
]
= u + 2
u3
3 + u5
5 + C
[Back substitute:u = sinh x]

Z
cosh5 x dx = sinh x +
2 sinh3 x
3 + sinh5 x
5 + C
b)
Integral to be evaluated is
Z x5
x2 16dx [x > 4]
To evaluate the integral, we make the following substitution
x = 4 cosh u
This implies
dx = 4 sinh u du
13
tabler-icon-diamond-filled.svg

Paraphrase This Document

Need a fresh take? Get an instant paraphrase of this document with our AI Paraphraser
Document Page
Therefore
Z x5
x2 16dx =
Z 45 cosh5 u
p 16 cosh2 u − 16
· 4 sinh u du
= 45
Z cosh5 u
p cosh2 u − 1 sinh u du
[Trig. Identity: sinh2 u = cosh2 u − 1]
= 1024
Z cosh5 u
sinh u sinh u du
= 1024
Z
cosh5 u du
[Using the result for
Z
cosh5 x dx, from part a)]
= 1024 sinh u +
2 sinh3 u
3 + sinh5 u
5 + C
[Back substitute: u = cosh1 x
4 ]
= 1024 sinhcosh1 x
4 + 2 × 1024 sinh3 cosh1 x
4
3
+ 1024 sinh5 cosh1 x
4
5 + 1024C
[Trig. Property:sinh cosh1 x
4 =
x2 16
4 , for positive x]
[Trig. Property:sinh3 cosh1 x
4 = (x2 16)3/2
64 , for positive x]
[Trig. Property:sinh5 cosh1 x
4 = (x2 16)5/2
1024 , for positive x]
= 1024
x2 16
4 + 2 × 1024
3 × 64(x2 16)3/2 + 1
1024 × 5
(x2 16)5/2 + C0
[where, C0 = 1024C]

Z x5
x2 16dx = 256
x2 16 +
32
3 (x2 16)3/2 + (x2 16)5/2
5 + C0
14
Document Page
Q 6.
dx
dt = t
(t2 + 1)1/3
Answer
a)
Since the Differential equation is of the form
dx
dt = p(x)
q(t)
we can apply the Variable Separable method to solve it.
b)
The DE is solved in the following way
dx
dt = t
(t2 + 1)1/3
[Separating variables]
dx = t
(t2 + 1)1/3 dt
[Integrating both sides]
Z
dx =
Z t
(t2 + 1)1/3 dt
[Substitute: t2 + 1 = u = 2t dt = du]
Z
dx = 1
2
Z du
u1/3
[Standard Int.
Z
un = un+1
n + 1
]
x = 1
2
u2/3
2/3 + C
[Back substitute: u = t2 + 1]
15
Document Page
x(t) = 3
4(t2 + 1)2/3 + C
c)
Initial condition:x(0) = 1.Therefore, substituting t = 0 in the solution for
x(t) (refer part b):
x(0) = 1 =
3
4((0)2 + 1)2/3 + C = 3
4 + C
Implies, C = 1 3
4 = 1
4. Therefore, the particular solution is
x(t) = 3
4(t2 + 1)2/3 + 1
4
Q 7.
dy
dt = −et+y, [t ≥ 0]
Answer
a)
Using property of exponential functions
ea+b = ea · eb
the DE is simplified as dy
dt = −ey et
This is similar to the form
dy
dt = p(y) q(t)
which is solved using Variable Separable method.
16
tabler-icon-diamond-filled.svg

Secure Best Marks with AI Grader

Need help grading? Try our AI Grader for instant feedback on your assignments.
Document Page
b)
The DE is solved in the following way
dy
dt = −ey et
[Separating Variables]
dy
ey = −et dt
[Integrating both sides]
Z dy
ey =
Z
et dt
[Standard Int.
Z
eax = eax
a ]
e1
1 = −et + C
ey = et + C
[Taking log on both sides]
y = ln (et + C)
y(t) = ln (et + C)
c)
Initial condition:y(0) = 2.Therefore, substituting t = 0 in the solution for
y(t) (refer part b):
y(0) = 2 = ln (e0 + C) = ln (1 + C)
Implies,
ln (1 + C) = 2 = 1 + C = e2 =⇒ C = e2 1
Therefore, the particular solution is
y(t) = ln (et + e2 1)
Q 8.
dy
dx = 3y
x + 1
17
Document Page
Answer
a)
The given DE has a form similar to
dy
dx + p(x)y = q(x)
with, p(x) = 3
x and q(x) = 1.
It is therefore a linear first order differentialequation whose solution is de-
termined the method of Integrating factor.
b)
Begin with the DE expressed correctly in the form of linear first order DE:
dy
dx 3y
x = 1 (1)
Comparing with the standard form oflinear first order DE,p(x) = 3
x .
Therefore, the integrating factor is
μ(x) = e
R p(x) dx = e3R 1
x dx = e3 ln x= eln( 1
x3 ) = 1
x3
Multiply (1) throughout by (x)
1
x3
dy
dx 3y
x4 = 1
x3
The left side is an exact differential ofy
x3 , that is
d
dx
y
x3 = 1
x3
dy
dx 3y
x4
18
Document Page
Therefore,
d
dx
y
x3 = 1
x3
[Integrating both sides]
Z d
dx
y
x3 =
Z 1
x3
[Fundamental Theorem:
Z d
dxf = f ]
[Standard Int. :
Z
xn = xn+1
n + 1
]
= y
x3 = 1
2x2 + C
y(x) = Cx3 x
2
Q 9.
dv
dx = k
v
Answer
a)
The DE is dv
dx = k
v, [k, v > 0& x ≥ 0]
Denote the starting point of the object as x0. The coordinate system can be
fixed at x0 such that origin (0, 0) is the starting point and when the object
moves away from the starting point, the change in distance is x − x0 = x.
19
tabler-icon-diamond-filled.svg

Paraphrase This Document

Need a fresh take? Get an instant paraphrase of this document with our AI Paraphraser
Document Page
The DE is solved in the following way
dv
dx = k
v
[Separating variables]
v dv = k dx
Integrating both sides
Z
v dv = k
Z
dx
v2
2 = kx + C
[Expressing in implicit form]
v(x) = 2kx + C0 [where,C0 = 2C]
b)
The speed of the object at the starting point is 10 m/s, that is when x = 0,
the speed v = 10.Implies,
v(0) = 10 =
p 2k(0) + C0 = C0 =⇒ C 0 = 100
The particular solution therefore is
v(x) = 2kx + 100
c)
When x = 5, the speed v = 20 m/s.Therefore,
20 =p 2k(5) + 100 = 400 = 10k + 100 =⇒ k = 30
Therefore, the complete solution for speed is
v(x) = 60x + 100
d)
When v = 40, the corresponding position of object is determined as
40 = 60x + 100 = 1600 = 60x + 100 =⇒ x = 25
20
Document Page
Therefore, the object is 25 m away from the starting point when its speed is
40 m/s.
e)
References:
B, G., Hass,J., Heil, C. R. and Weir,M. D. (2018). Thomas’calculus:
multivariable.Boston:Pearson.
Blitzer, R. (2019).Thinking mathematically (7th ed.).Boston:Pearson.
Clark, W. D. and Mccune,S. K. (2013).Linear algebra.New York,New
York: Mcgraw Hill.
Grewal,B. (2017). Advanced Engineering Mathematics.India: Mercury
LearningInformation.
21
Document Page
Hoffman,K. and Kunze,R. (2015). Linear algebra.Noida,U.P., India:
Pearson India Education Services.
Lipschutz, S. and Lipson, M. (2018).Linear algebra.New York:Mcgraw-Hill
Education.
Maruskin, J. M. (2014).Integralcalculus.San Jose, California:Solar Crest
Publishing, Llc.
Stewart, J. (2019).Calculus:concepts and contexts.Boston, Ma, Usa:Cen-
gage.
Stewart,J., Redlin, L., Watson,S. and Panman,P. (2017). Precalculus:
mathematics for calculus.Australia:Cengage Learning.
Sullivan, M. (2019).Precalculus.Hoboken, NJ: Pearson.
22
chevron_up_icon
1 out of 22
circle_padding
hide_on_mobile
zoom_out_icon
[object Object]

Your All-in-One AI-Powered Toolkit for Academic Success.

Available 24*7 on WhatsApp / Email

[object Object]